(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Oral health significantly influences overall well-being, with dental caries and periodontal diseases posing global health challenges. Mouthwashes play a critical role in the non-mechanical control of dental plaque, pivotal in preventing these diseases. Despite their importance, the knowledge and practices of dental practitioners concerning mouthwash use, particularly in the Qassim region, Saudi Arabia, vary widely. Objectives: This study aims to assess the knowledge and practices related to mouthwash use among dental practitioners in the Qassim region, to identify gaps in knowledge, and to explore the influence of demographic factors on these practices. Methods: A cross-sectional survey was conducted using a standardized online questionnaire distributed to 152 registered dental practitioners in the Qassim region. The survey included multiple-choice, Likert scale, and open-ended questions to evaluate knowledge about mouthwash types, indications, and potential side effects. Data were collected over six months, from January to June 2024, and analyzed using SPSS version 25.0. Results: The majority of practitioners (46.7%) recommended using mouthwash twice daily, with 71.7% advising its use post-brushing. A significant portion, however, displayed variability in the timing and duration of mouthwash application, with 26.3% recommending pre-brushing usage. About 65.8% of the participants acknowledged the need for more detailed educational programs about mouthwashes. Notably, younger practitioners tended to adhere more strictly to the twice-daily usage guideline, reflecting recent training impacts. Cultural factors such as the use of Siwak also influenced the recommendations. Conclusion: The findings highlight a broad range of practices and a substantial variability in the knowledge among dental practitioners regarding the optimal use of mouthwashes. This underscores the necessity for enhanced educational initiatives targeted at standardizing practices based on the best available evidence. Such efforts are crucial for improving oral healthcare outcomes and aligning practices with global standards.